Study on extraction and stability of natural red colorant from hibiscus sabdariffa l. - Chan, William (2014)
Hibiscus Sabdariffa L. which is also known as Roselle is a tropical shrub that contains anthocyanins, which is responsible for the red colour appearance of the fruit. The major anthocyanins found in Roselle are delphinidin-3-sambubioside and cyanidin-3-sambubioside, while the minor anthocyanin is cyanidin-3-glucoside. Its application in the food industry is wide and includes products such as jam, beverage drink and fruit juice. However, the application of Hibiscus Sabdariffa L. as a source of natural food dye has never been studied. The objective of the study is to use hot water extraction method to extract the anthocyanin from Hibiscus Sabdariffa L. and to study the stability of the extract. Hot water extraction method was used to extract anthocyanin. 4g of dried Roselle calyces and 100mL of distilled water was mixed and the extraction was done using shaking water bath. UV-Vis analysis were done on the samples and results show that the optimal temperature and time found for the extraction process is between the range of 50°C - 60°C and 15 minutes. As for the stability of anthocyanin, the addition of food grade stabilizers such as maltodextrin DE15-20 and trehalose proved that it could retard the degradation of anthocyanin with results showing maltodextrin DE15-20 as the better stabilizer. Lastly, all the samples tested with HPLC showed that cyanidin-3-glucoside were present in all the samples